2023
DOI: 10.1007/s10570-023-05374-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments of the nanocellulose extraction from water hyacinth: a review

Abstract: Nanocellulose, an exceptional natural material acquired from cellulose, has received tremendous attention over the past decades. This is because of its unique physical characteristics, surface chemistry, functional properties, and biocompatibility. Cellulose nanocrystals (CNCs) and cellulose nanofibers (CNFs) are two major types of nanocellulose that have received key interest so far. Nanocellulose is commercially produced from wood-based sources. With the ongoing demand for nanocellulose, agricultural wastes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…91 This method involves grinding, chopping or milling lignocellulosic biomass to produce smaller particle sizes, preparing the lignocellulosic material for a more effective chemical pretreatment process. 107 Although no chemicals are used during the physical treatment of nanocellulose, factors such as temperature, pressure, feedstock type, and retention time are significantly important because they could influence their outcomes. 18,91,108 On the other hand, chemical pretreatment weakens intermolecular bonds and removes excess wax, lignin, and hemicellulose present in the lignocellulosic material.…”
Section: Nanocellulose Extraction Processmentioning
confidence: 99%
“…91 This method involves grinding, chopping or milling lignocellulosic biomass to produce smaller particle sizes, preparing the lignocellulosic material for a more effective chemical pretreatment process. 107 Although no chemicals are used during the physical treatment of nanocellulose, factors such as temperature, pressure, feedstock type, and retention time are significantly important because they could influence their outcomes. 18,91,108 On the other hand, chemical pretreatment weakens intermolecular bonds and removes excess wax, lignin, and hemicellulose present in the lignocellulosic material.…”
Section: Nanocellulose Extraction Processmentioning
confidence: 99%
“…As green materials, cellulose and lignin of aquatic plant origin have the advantages of being environmentally friendly and sustainable, and they are often used to make separators or adsorbents [1]. However, the sorption performance and extraction concentration efficiency of cellulose and lignin materials are low, and there is an upper limit to the improvements in performance that can be achieved by simply relying on derivatives or changing their presentation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this species can absorb many different substances from its aquatic environment, including essential nutrients, such as nitrogen, phosphorus, potassium, calcium, magnesium, and also toxic elements [14]. The contents of cellulose, hemicelluloses, lignin, and available proteins can play a vital role in the plant's capacity to absorb metal trace elements (MTEs) and other water pollutants [15,16]. It has been demonstrated that aquatic plants can efficiently remove MTEs from aqueous solutions [17].…”
Section: Introductionmentioning
confidence: 99%